Protective Effects of Olanzapine on Irradiation-Induced Pulmonary and Cardiac Injury in Mice: A Histopathological Evaluation - Ali Mirmahdi; Mansoureh Mirzaei; Seyed Jalal Hosseinimehr; Abbas Ali Karimpour Malakshah; Hooman Zarei; Fereshteh Talebpour Amiri (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Radiation therapy (IR) is a standard treatment for various thoracic malignancies. However, radiation-induced pulmonary and cardiac injuries can be life-threatening complications in these patients. Olanzapine (OLZ) is an atypical antipsychotic drug that exhibits antioxidant properties at low doses. The aim of this study was to evaluate the histopathological changes associated with radiotherapy-induced pneumonitis and cardiac injury, and to assess the protective effects of olanzapine against these conditions. Materials and methods: In this experimental study, 30 BALB/c mice were randomly assigned to six groups: Control, IR (6 Gy, single dose on the eighth day of the study), OLZ (10 and 20 mg/kg for 10 consecutive days), IR+ OLZ (10 mg/kg), and IR + OLZ (20 mg/kg). Histopathological analysis was performed to assess structural changes in the myocardium and lungs on day 11 of the study. Data were analyzed using GraphPad Prism software, and statistical comparisons were made using one-way ANOVA followed by Tukey's post hoc test. Results: Our data showed that radiotherapy induced cardiac and pulmonary injury. Histopathological analysis revealed that olanzapine ameliorated structural cardiac damage, including fibrosis and macrophage infiltration, in irradiated mice. In lung histology, olanzapine reduced interstitial edema, inflammatory cell infiltration, alveolar wall thickening, alveolar collapse, and vascular congestion. Semi-quantitative evaluation demonstrated that the 20 mg/kg dose was more effective than the 10 mg/kg dose and the radiation-only group in improving the tissue structure of both the heart and lungs. Conclusion: Overall, our study demonstrated the protective effects of olanzapine treatment against pulmonary and cardiac injuries, as evidenced by improvements in histological structure.